The extent to which the Iraqi environment responds to the requirements of IAS 12 in determining income tax: بحث تطبيقي في الهيئة العامة للضرائب/ قسم الشركات (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The importance of this research comes from the possibility of achieving positive interaction between accounting and tax through the interest in setting accounting standards and adapting them to local tax legislation, as the adoption of the application of the international standard (IAS 12) for income taxes helps to measure and determine the base for income tax and may lead to an increase in the tax outcome. Through the reliance of enterprises on many accounting bases, and that the tax administration in Iraq depends on the element of personal judgment in determining the tax base, which leads to lack of objectivity in determining the tax outcome, as the impact of the accounting standard (IAS 12) on the tax base and tax outcome is one of the most Technical means in making the tax system in Iraq the most flexible as an objective guideline in determining the tax outcome. Accurately and credibly correct and thus determine the tax proceeds, which are the important sovereign resource for the state. We see the possibility of compatibility between the (IAS 12) standard in determining the taxable income reliably and the Iraqi Income Tax Law No. (113) for the year 1982 (amended) and its amendments, and the regulations and instructions for determining the expenses deducted from income or revenues that are added to income, and through that A number of conclusions were reached, the most important of which are:1-Contributes to unifying the process of tax accounting on income in order to address the differences between accounting income and tax income.2- It will lead to attracting investments by foreign companies, which will be positively reflected on the tax returns approved as a source of financing the Iraqi state's general budget.3- The adoption of the International Accounting Standard (IAS 12) in determining the tax base increases the quality and quality of the accounting information provided to different categories of users by addressing the differences between accounting profit and tax profit.Through these conclusions, the researcher made several recommendations, including:1- It requires the Accounting and Regulatory Standards Board and professional institutions in Iraq to work on providing the requirements for the application of international standards, the International Accounting Standard (IAS 12), which will be applied in all governmental and private sectors as it is of great importance to local and foreign companies.2-he necessity of adopting the application of the International Accounting Standard (IAS 12) Income Taxes because it increases the tax revenues used as a source of financing the general budget of the Iraqi state and also achieves a set of benefits for companies, investors, local governments and society.